Single intra-articular injection of high concentrated hyaluronic acid – A pilot study in horses - Monteiro, SO; Bettencourt, EV; Branco, SM; Lepage, OM (Proceedings of ECVS Annual Scientific Meeting, 5-7 de Julho 2018, Atenas, Grécia, 2018)
Distal limb osteoarthritis (OA) is a common cause of lameness in horses and hyaluronic acid (HA) is frequently used, alone or in combination with other drugs, for intra-articular (IA) treatment. Therefore, we decided to investigate a product with high concentration of high molecular weight (HMW)-HA for a single IA injection that has been approved for humans (Goldenberg, 2014). The aim of this study was to assess the treatment efficacy and safety in horses using a body mounted inertial sensor device technology and synovial fluid (SF) analysis before and after treatment. In conclusion, our results suggest that high concentration of a single IA injection of HMW-HA in horses is safe, induce modest subjective lameness and asymmetry improvement and reduces TP in SF. This could represent an alternative, in the short-term period, to drugs that are forbidden in competition for pain relief while preserving joint metabolism. A randomized, double blind and controlled study, with a larger number of horses should be performed in order to confirm the clinical interest of this therapy.
Keywords: hyaluronic acid; horses; intra-articular